Information technology - Security techniques - Code of practice for protection of personally identifiable information (PII) in public clouds acting as PII processors - International Organization for Standardization (ISO) (ISO)
Scope -- Normative references -- Terms and definitions -- Overview -- Information security policies -- Organization of information security -- Human resource security -- Asset management -- Access control -- Cryptography -- Physical and environmental security -- Operations security -- System acquisition, development and maintenance -- Supplier relationships -- Information security incident management -- Information security aspects of business continuity management -- Compliance --